Application of Serious Games in Health Care: Scoping Review and Bibliometric Analysis - Wang, Yue; Wang, Zhao; Liu, Guoqing; Wang, Zhangyi; Wang, Qinglong; Yan, Yishan; Wang, Jing; Zhu, Yue; Gao, Weijie; Kan, Xiangling; Zhang, Zhiguo; Jia, Lixia; et al. (Frontiers in Public Health, 2022)
Background Serious games (SGs) as one kind of intervention that can improve the level of knowledge and change behavior to affect health outcomes has been increasingly applied in health care. Objective Analyze hotspots and trends of the application of SGs in health care and provide reference and direction for further research in the future. Methods The Web of Science (WoS) Core Collection database was used for extracting the literature on SGs in health care for the period from the database established to 11 October, 2021. Scoping review and bibliometric analysis were used to deeply analyze and visualize countries, categories of studies, annual study output, cited authors, cited journals, cited articles, and keywords of healthcare field. Results A total of 1,322 articles were retrieved, then every articles' title and abstract were read one by one, and 795 articles were included after screening with an exponential increase in publication volume. The United States of America made the greatest contribution to global publications regarding SGs in health care. From the total, 20.8% of articles fall under the category of health care sciences services. The target groups were mainly concentrated in children (18.0%), youth (13.8%), the elderly (10.9%), adolescents (9.1%), and adults (3.4%). Baranowski T (n = 103 citations) is the most influential author, followed by Kato PM (n = 73 citations) and Desmet A (n = 58 citations). The top three cited journals were “Plos One” (n = 268 citations), “Games for Health Journal” (n = 209 citations), and “Journal of Medical Internet Research” (n = 197 citations), and the top three cited articles were “A meta-analysis of serious digital games for healthy lifestyle promotion,” “A Systematic Review of Serious Games in Training Health Care Professionals,” and “Video game training enhances cognitive control in older adults.” More and more studies focus on specific age groups, such as children, adolescents, and the elderly. The research hotspots and trends included “rehabilitation,” “medical education,” and “design.” Conclusions The application of SGs in health care remains important areas for future research. “Rehabilitation,” “medical education,” and “design” reflected the latest research hotpots and future trends.